2022
DOI: 10.3390/cancers14205165
|View full text |Cite
|
Sign up to set email alerts
|

Ixazomib, Lenalidomide and Dexamethasone in Relapsed and Refractory Multiple Myeloma in Routine Clinical Practice: Extended Follow-Up Analysis and the Results of Subsequent Therapy

Abstract: Background: We confirmed the benefit of addition of ixazomib to lenalidomide and dexamethasone in patients with relapsed and refractory multiple myeloma (RRMM) in unselected real-world population. We report the final analysis for overall survival (OS), second progression free survival (PFS-2), and the subanalysis of the outcomes in lenalidomide (LEN) pretreated and LEN refractory patients. Methods: We assessed 344 patients with RRMM, treated with IRD (N  =  127) or RD (N  = 217). The data were acquired from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, a significant OS benefit was not observed in the final analysis, possibly due to the type of subsequent lines of therapies including an inferior proportion of patients in the IRd group who received daratumumab‐based compared with the Rd group 43 . Real‐world studies have confirmed the effectiveness and safety of IRd in the routine clinical practice in accordance with the clinical trial results 44–47 . Interestingly, pharmacoeconomic analyses both in the United States of America and in Europe have suggested that all‐oral IRd regimen is among the least expensive approved triplet regimens for patients with RRMM 48,49 …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, a significant OS benefit was not observed in the final analysis, possibly due to the type of subsequent lines of therapies including an inferior proportion of patients in the IRd group who received daratumumab‐based compared with the Rd group 43 . Real‐world studies have confirmed the effectiveness and safety of IRd in the routine clinical practice in accordance with the clinical trial results 44–47 . Interestingly, pharmacoeconomic analyses both in the United States of America and in Europe have suggested that all‐oral IRd regimen is among the least expensive approved triplet regimens for patients with RRMM 48,49 …”
Section: Discussionmentioning
confidence: 88%
“…43 Real-world studies have confirmed the effectiveness and safety of IRd in the routine clinical practice in accordance with the clinical trial results. [44][45][46][47] Interestingly, pharmacoeconomic analyses both in the United States of America and in Europe have suggested that all-oral IRd regimen is among the least expensive approved triplet regimens for patients with RRMM. 48,49 The combination of Dara-Ixa-dex has been also evaluated in the first-line treatment of patients with NDMM who are not fit for ASCT.…”
mentioning
confidence: 99%
“…In the routine clinical practice, the all‐oral route of administration and the favorable safety profile make this regimen potentially suitable for the treatment of elderly pts with comorbidities and/or impaired PS 5,6 . Several observational studies have indeed reported a higher prevalence of older age, impaired PS, advanced stage disease, >2 pLoT in the real‐world population treated with IRd, showing comparable effectiveness with OR rates ranging from 60% to 74% and mPFS ranging from 11.4 to 43 m 7–15 . Moreover, a significant proportion of pts (17%–39%) in the real‐world setting has previous exposure to Len compared to only 12% in the MM1 study.…”
Section: Discussionmentioning
confidence: 99%
“…In the routine clinical practice, the all-oral route of administration and the favorable safety profile make this regimen potentially suitable for the treatment of elderly, frail patients (pts) [2][3][4] who are under-represented in the clinical studies. 5,6 Several observational studies [7][8][9][10][11][12][13][14][15] of IRd have confirmed the effectiveness of IRd with ORR ranging from 60% to 74% and mPFS from 11.4 to 27.6 m in real-world setting, despite a higher prevalence of elderly and heavily pre-treated pts, compromised performance status (PS), and advanced stage disease. A proportion of pts ranging from 17% to 38% in the published real-world studies had previous exposure to lenalidomide (Len) compared with only 12% in the MM1 study.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, these findings are consistent with those reported in other real-world observational studies of IRd in patients with RRMM. 6,[8][9][10][11][12][13] Lenalidomide-containing regimens and proteasome inhibitors (PIs) are used commonly across lines of therapy (LoTs) for the treatment of patients with MM. 14 Although data on effectiveness outcomes following retreatment with agents used in earlier LoTs are limited, there is some evidence to suggest that patients may derive benefit from retreatment with an agent they have been previously exposed to (but are not refractory to).…”
Section: Introductionmentioning
confidence: 99%